(untitled) (Journal of the Spanish Institute for Strategic Studies, 2023)
The main purpose of this article is to offer a perspective on the incidence of nuclear terrorism in Spain’s National Security Strategy. Although the existing antecedents on this type of terrorism in Spain are scarce, its relevance in the context of the instruments that States have currently equipped to maintain a security situation cannot be denied. Nuclear terrorism exists and the main actors of the international community consider it a serious threat and dedicate great efforts to prevent this threat from passing from power to act. In this way, it is intended to analyze the way in which this threat has been treated in the aforementioned Strategy over time until reaching the latest version of 2021, and its annual update included in the last Annual National Security Report of 2020.